Breastfeeding and Depression: A Systematic Review of the Literature - CHATZI, KLEONIKI; ANTONIOU, EVANGELIA; DAGLA, MARIA; OROVOU, EIRINI; SARELLA, ANGELIKI; PALASKA, ERMIONI; ILIADOU, MARIA (International Journal of Innovative Research in Medical Science, 2022)
This review examines the association between postpartum depression and breastfeeding in the context of studies published between 2015 and 2022. The goal of those studies was to determine the impact of depression on breastfeeding and vice versa. After conducting in-depth research on 15 studies that varied in location, population, and method of evaluation, a high degree of agreement was observed in their findings. Postpartum depression has a significant impact on breastfeeding percentages, whereas breastfeeding appears to improve the mother's psychological status and significantly reduce anxiety and depression symptoms. These findings emphasize the complex relationship between postpartum depression and breastfeeding and validate the need for additional research.